PENERAPAN KESELAMATAN DAN KESEHATAN KERJA DI PT. GANDA ALAM MAKMUR - Agrivina Putri Priliani; Sintorini Moerdjoko; Diana Irvindiaty Hendrawan (Jurnal Lingkungan dan Kota, 2022)
PT. Ganda Alam Makmur is a coal company in East Kalimantan. PT. Ganda Alam Makmur has conducted an assessment of the mining safety management system such as controlling mining safety risks including occupational safety and health in mining and safety in mining operations. This study aim to determine the effect of the Occupational Health and Safety Management System as an effort to improve Good Mining Practice at PT. Ganda Alam Makmur is carried out by evaluating the health and safety management system implemented in an effort to improve Good Mining Practice. The method in this study is gap analysis to determine the system of implementing occupational health and safety. The results of the gap value at PT. Ganda Alam Makmur is 20% where the organization is ready to complete an occupational health and safety management system.